1996
DOI: 10.1002/etc.5620151021
|View full text |Cite
|
Sign up to set email alerts
|

Persistent synthetic chlorinated hydrocarbons in albatross tissue samples from midway atoll

Abstract: Anthropogenic organic contaminants have been found in even the most remote locations. To assess the global distribution and possible effects of such contaminants, we examined the tissues of two species of albatross collected from Midway Atoll in the central North Pacific Ocean. These birds have an extensive feeding range covering much of the subtropical and northern Pacific Ocean. Anthropogenic contaminants were found at relatively great concentrations in these birds. The sum of 19 polychlorinated biphenyl (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…The other CBs of importance were CB-126<CB-77<CB-156<CB-105<CB-118<CB-169 [158]. Occurrence of non-, mono-, di-ortho CBs, and PCDD/Fs have been detected in albatrosses living in pristine locations such as Midway Atoll in the Pacific Ocean [159]. Their study confirmed an earlier prediction by Kannan et al [12] that impact of planar PCBs and PCDFs will be greater than PCDDs in organisms living far away from land.…”
Section: Birdssupporting
confidence: 71%
“…The other CBs of importance were CB-126<CB-77<CB-156<CB-105<CB-118<CB-169 [158]. Occurrence of non-, mono-, di-ortho CBs, and PCDD/Fs have been detected in albatrosses living in pristine locations such as Midway Atoll in the Pacific Ocean [159]. Their study confirmed an earlier prediction by Kannan et al [12] that impact of planar PCBs and PCDFs will be greater than PCDDs in organisms living far away from land.…”
Section: Birdssupporting
confidence: 71%
“…Thus, concentrations of PCBs have decreased by a factor of two over the past 25 years. [10,11]. The birds sampled in the current study were killed in the early part of the breeding cycle when fat reserves were greatest.…”
Section: Resultsmentioning
confidence: 99%
“…The diet of the Laysan albatross consists primarily of ommastrephid squids (∼68% of the diet) whereas the black‐footed albatross feed mostly on flying fish (50%) and squids constitute a relatively lesser proportion (32%) of the diet. Details regarding the sources of environmental contaminants for these two species of albatrosses have been reported previously [41,42].…”
Section: Resultsmentioning
confidence: 99%